How to conduct valuable marketing research with neurophysiological tools - Bigne, E.; Boksem, M.; Casado‐Aranda, L. A.; García‐Madariaga, J.; Gier‐Reinartz, N. R.; Guerreiro, J.; Loureiro, S.; Kakaria, S.; Smidts, A.; Wedel, M. (Psychology and Marketing, 2025)
Consumer neuroscience is gaining attention in the marketing field. The growing interest calls for a framework integrating neuroscience in marketing. This paper aims to serve as a practical guide for conducting consumer research using neurophysiological tools. The paper is organized into three main sections. The first section presents a framework for categorizing types of consumer neuroscience research based on four primary research objectives. The following section describes the use of neurophysiological tools in marketing and addresses their roots in their mother disciplines. Specifically, we address electrocardiography, galvanic skin conductance, eye-tracking, electroencephalography, functional magnetic resonance imaging, and functional near-infrared spectroscopy. Additionally, we refer to emerging measurements from hormones and genes. Likewise, this section highlights the most influential papers, equipment facilities, and software on each tool to support researchers who need to become more familiar with any of those techniques. Third, this paper introduces an integrative framework for consumer neuroscience research in marketing, covering research aims, types of stimuli, changes in organisms, and consumer response processes. In addition to core neuroscience citations, the paper incorporates specific marketing-relevant consumer neuroscience papers to guide research in the marketing field.